2020
DOI: 10.20517/2347-9264.2020.151
|View full text |Cite
|
Sign up to set email alerts
|

Periocular rejuvenation using hyaluronic acid fillers

Abstract: The eyes and periocular region are critical for emotive display and play a key role in social interactions. This region includes the upper and lower eyelids, brow-lid complex, and lid-cheek complex. Perturbances in this area can lead to a prematurely aged appearance and patients complain of emotive misinterpretation. It often shows the earliest signs of facial aging, leading to a tired, sad, or angry appearance. With the evolution of medical and surgical knowledge on facial aging, there has been a shift from i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
1
0
2
Order By: Relevance
“…It has been reported that HA with a higher molecular weight and viscosity provides a better volumetric augmentation for deep facial injections, and products with low molecular weight should be preferred for superficial subcutaneous injections. [ 29 ] However, this study indicates that it is safer to use low-viscosity and low-molecular-weight HA, even if the injection is performed in the deep supraperiosteal plane in the upper eyelid. Performing injections in this area using thin cannulas or syringe needles and high-viscosity products increases the injection pressure.…”
Section: Discussionmentioning
confidence: 87%
“…It has been reported that HA with a higher molecular weight and viscosity provides a better volumetric augmentation for deep facial injections, and products with low molecular weight should be preferred for superficial subcutaneous injections. [ 29 ] However, this study indicates that it is safer to use low-viscosity and low-molecular-weight HA, even if the injection is performed in the deep supraperiosteal plane in the upper eyelid. Performing injections in this area using thin cannulas or syringe needles and high-viscosity products increases the injection pressure.…”
Section: Discussionmentioning
confidence: 87%
“…Discussão Fisioterapia Brasil 2021;22 (6):904-911 Este estudo analisou o uso de terapia ultrassônica em duas pacientes voluntárias, apresentando rugas periorbitais, dermatocalase e flacidez palpebral. Os achados deste estudo mostraram que a terapia com US foi visivelmente positiva aos pesquisadores e considerados muito satisfatórios pelas participantes.…”
Section: Figura 2 -Foto Da Voluntária Caso 2 No Momento a Antes Do In...unclassified
“…O ultrassom (US) tem se mostrado um método seguro e eficaz para melhorar a flacidez da pele, por meio da coagulação e retração do tecido dérmico. Por isso o US também pode ser uma opção para o rejuvenescimento facial de regiões delicadas, como as áreas periorbiculares [6]. Assim o objetivo deste trabalho foi relatar em um estudo de casos de correção da dermatocalase, por procedimento estético não invasivo com ultrassom.…”
Section: Introductionunclassified